2009
DOI: 10.1242/jcs.050344
|View full text |Cite
|
Sign up to set email alerts
|

Myosin-Va-interacting protein, RILPL2, controls cell shape and neuronal morphogenesis via Rac signaling

Abstract: Rac1 form a complex, and that RILPL2 is able to induce activation of Rac1 and its target, p21-activated kinase (Pak). Notably, both RILPL2-mediated morphological changes and activation of Rac1-Pak signaling were blocked by expression of a truncated tail form of MyoVa or MyoVa shRNA, demonstrating that MyoVa is crucial for proper RILPL2 function. This might represent a novel mechanism linking RILPL2, the motor protein MyoVa and Rac1 with neuronal structure and function.Supplementary material available online at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 82 publications
0
29
0
2
Order By: Relevance
“…The Rilpl2 constructs were identical to those used in a previous study (ΔC, aa 1–113; ΔN, aa 114–197; Lisé et al ., 2009). Sequence alignment was used to divide Rilpl1 at positions equivalent to those in Rilpl2 (ΔC, aa 1–288; ΔN, aa 289–406).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Rilpl2 constructs were identical to those used in a previous study (ΔC, aa 1–113; ΔN, aa 114–197; Lisé et al ., 2009). Sequence alignment was used to divide Rilpl1 at positions equivalent to those in Rilpl2 (ΔC, aa 1–288; ΔN, aa 289–406).…”
Section: Resultsmentioning
confidence: 99%
“…Sequence alignment was used to divide Rilpl1 at positions equivalent to those in Rilpl2 (ΔC, aa 1–288; ΔN, aa 289–406). The ΔC construct of both proteins contains the RH1 domain and in Rilpl2 the MyoVa interaction domain (Lisé et al ., 2009). The ΔN construct of both proteins contains the RH2 domain and the Rab36 interaction domain (Figure 1A; Matsui et al ., 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because PTEN loss has also been shown to alter the migration of neurons and to increase dendritic arborization and spine density (49), it would be interesting to determine if the loss of myosin Va alters these neuronal properties as well. Relevant to this, however, the dendritic arborization of cultured Purkinje neurons (29) and the density of spine-like protrusions of cultured hippocampal neurons (52) are decreased rather than increased upon interfering with myosin Va function. The latter study further showed that myosin Va binds the Rac1 activator RILPL2, which exhibits, in a myosin Va-dependent manner, a positive effect on the formation of spine-like protrusions in hippocampal neurons (52).…”
Section: Myosin V Controls Neuronal Cell Size By Translocating Pten Tmentioning
confidence: 93%
“…In S. cerevisiae, the myo2p-binding sites of organelle and vesicle-specific adaptors have been mapped onto the GTD region (7,8). In mammals, MyoV-GTD directly interacts with several adaptor proteins, including melanophilin (MLPH) (9)(10)(11), Rab interacting lysosomal protein-like 2 (RILPL2) (12), and granuphilin (13) for MyoVa, and Rab11-family interacting protein 2 (14) for MyoVb. As Rab-binding proteins (15)(16)(17)(18), these adaptors presumably function to link MyoV with specific Rab-attached membranous cargos for cargo loading and transport (to simplify, we use "cargos" instead of "cargo adaptors" here).…”
mentioning
confidence: 99%